Health care providers' perception of facilitators and barriers for the practice of skin-to-skin contact in Saudi Arabia: A qualitative study. (February 2020) - Abdulghani, Nawal; Edvardsson, Kristina; Amir, Lisa H.
Abstract: Objectives: To identify Health Care Providers' (HCPs') perceived facilitators, barriers and requirements for implementing the practice of Skin-to-Skin Contact (SSC) immediately after vaginal birth. Design: A descriptive qualitative study with semi-structured interviews. Two theoretical frameworks were used to guide the data analysis: Theoretical Domains and the Grol and Wensing's barriers to and facilitators of change in health care practice. Settings: Two public hospitals in Jeddah, Saudi Arabia with 7000 and 6000 births per year, respectively. Participants: A purposeful sample of 20 obstetricians, midwives, and nurses. Findings: The HCPs' perceived facilitators included buy-in of the practice of SSC. Existing or potential barriers included the absence of a detailed policy and guidelines to support the practice of SSC, lack of capabilities and motivations to implement the practice of SSC, mothers not interested in SSC, lack of professional collaboration, staffing and time constraints, and a medicalised birth environment that prioritised interventions over SSC. Conclusion and implication to practice: The insights gained from identification of facilitators and barriers for SSC practice in this study can assist the development of a tailored multi-level implementation strategy at the individual, social and organisational levels to provide continuous uninterrupted SSC immediately after birth. The practice of SSC could likely be successfully implemented if there is multidisciplinary collaboration that prioritises the practice of SCC.